The Selection of the Language in Indonesian Learning at SMK Multi Karya Medan - Ruth Remilani Simatupang; Muhammad Rohmadi; Kundharu Saddhono (Universitas Indraprasta PGRI, 2018)
This study aims to describe the function the code switching used by speakers at SMK Multi Karya Medan. This research is a descriptive qualitative research. The subjects in this study were the teacher and the students. The objects were the utterances of code-switching in Indonesian language learning in SMK Multi Karya Medan. Validity data technique is used triangulation of data source and informant review. Data collection is using listen and speak methods. Data analysis using the intralingual method. The result of the research showed that the function of code-switching at the time of the process of Indonesian language learning are emphasized, reprimanded, reminded, explained, asked and commanded.